Optimization of Digital Marketing as an Effort to Expand the Reach of Promotion of MSME Products Assist by Village Enterprises Ngerangan Jaya - Akhmad Nurdin; Sabtun Ismi Khasanah; Joko Istiyanto; Sinta Rizky Anggraini; Lilik Patonah (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Currently MSME sector can be seen in everyday life, starting from face to face directly or through digital media. The digital era has changed people's social activities increasingly with the emergence of various digital social media, and the social media is a gathering place for individuals and groups who are active and communicate with each other, and has been a strategic part of a business's product. Ngerangan village is currently known as the forerunner village of angkringan, and beginning in mid-2021 through the Village Enterprises Ngerangan Jaya will develop the Ngerangan Tourism Village by utilizing the potential of each hamlet area, there are several MSME products and businesses produced are assist by the Village Enterprises Ngerangan Jaya. Based on the situation analysis and interviews with the management of the Village Enterprises Ngerangan Jaya, the Ngerangan Tourism Village has several problems, one of the problems of this tourist village is the lack of understanding of residents about the use of information technology in tourism development which plays a role in providing information. From the analysis of the situation, the purpose of this activity is to equip and provide training to active members of MSME in each hamlet in Ngerangan Village to utilize social media as a means of digital marketing. This community service activity was carried out in Ngerangan Village, Bayat District, Klaten Regency by the Politeknik Manufaktur Ceper Community Service Team.